Marguerite Yourcenar's Prefaces: Genesis as Self-effacement - Colette Gaudin (Studies in 20th & 21st Century Literature, 1985)
Most critics of Marguerite Yourcenar largely ignore the existence of the complex network of prefaces and postfaces which accompanies her fiction. On the basis of the success of her historical reconstitutions and of the classical perfection of her style they characterize her work either as the best illustration of a sexless literature or as a case of denial of femininity. But her prefaces cannot be read simply as an exposition of her thinking about history or as a linear history of her writing. While an authoritative voice exposes her method and asserts a will to aesthetic perfection, the writer as historical subject tends to efface this authority by insisting on the details and accidents that accompany every beginning and every genesis. The will to historical knowledge leads her to expose multiple lines of historicity which reveal, in the fragmented writing of the prefaces, the impossibility of maintaining the fiction of a unified subject, Her cogito could not be "I write, therefore I am." but "I write, therefore I am other."
Keywords: Marguerite Yourcenar; preface; postface; historical reconstitution; sexless literature; denial of femininity; femininity; history; linear thought; aesthetic; genesis; fiction; subject